COMPARATIVE STUDY OF ANTIMICROBIAL ACTIVITY OF LEMONGRASS (CYMBOPOGON CITRATUS), CLOVE (SYZYGIUM AROMATICUM), AND TULSI (OCIMUM) ESSENTIAL OILS AGAINST FOODBORNE PATHOGENS - MONIKA YADAV; ROOPAL DHAR; SOHINI SINGH; TANU ALLEN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present work aims to compare the essential oils (EOs) of Lemongrass (Cymbopogon citratus), Clove (Syzygium aromaticum), and Tulsi (Ocimum sp.) having antimicrobial activity and to find the most effective EO against different types of foodborne microorganisms. Methods: The EOs were investigated for its antimicrobial activity against different types of Gram-negative and Gram-positive bacteria such as Escherichia coli, Micrococcus luteus, Staphylococcus aureus, and Bacillus cereus and fungal strains such as Aspergillus niger, Candida albicans, Chaetomium globosum, and Penicillium funiculosum by agar well diffusion method. The antimicrobial actions of these EOs were evaluated by calculating the zone of inhibition. Results: Of the three EOs used in the study, the effect of clove oil was found greater against all the microorganisms followed by lemongrass and tulsi EOs. All the microorganisms used in the study were found sensitive to clove EO, wherein the highest zone of inhibition was observed in A. niger (41.56±5.05 mm) and P. funiculosum (40.34±4.83 mm), and C. globosum (39.53±1.69 mm) and smallest in S. aureus (9.77±0.93) and E. coli 1(11.07±0.52). Moreover, it was also found that EOs exhibit more sensitivity toward Gram-positive bacteria than Gram-negative bacteria. Conclusion: The successful effectiveness of EO can play an important role in resolving the major problem of human health arising due to the use of chemical preservative. It was found that EO of clove oil was the most effective against fungal and bacterial strains than lemongrass and tulsi EOs. Furthermore, clove oil is less costly than lemongrass and tulsi oil; it can be more economic and promising to be used as a food preservative against foodborne pathogens.